2009
DOI: 10.1017/s1368980008004242
|View full text |Cite
|
Sign up to set email alerts
|

Iodine status in a Sherpa community in a village of the Khumbu region of Nepal

Abstract: Objective: To assess the iodine status of Sherpa residents living in Kunde village, Khumbu region, Nepal. Design: Prevalence of goitre was determined by palpation. Urinary iodine concentrations (UIC) were determined in casual morning samples, and thyroidstimulating hormone (TSH) in finger-prick blood samples on filter paper. Dietary and demographic data were obtained via questionnaire, and selected foods analysed for iodine. Setting: Khumbu region is an area of low soil iodine in Nepal, where the prevalence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
4
5
1
Order By: Relevance
“…On the other hand, five subjects (14.7%) among them were diagnosed as having HID. The incidence of HID is surprisingly low in view of the extremely low iodine intake but may actually be in line with other data from population studies [9][10][11][12][13][14] or may reflect difficulty in recognizing hypothyroid state in these patients or may be due to thyroid adaptive processes [15][16][17][18]. Possibly SMID patients, the targets of this study, might be at risk of developing disorders with a poor response of TSH that renders their hypothyroidism difficult to diagnose.…”
Section: Stagesupporting
confidence: 84%
See 1 more Smart Citation
“…On the other hand, five subjects (14.7%) among them were diagnosed as having HID. The incidence of HID is surprisingly low in view of the extremely low iodine intake but may actually be in line with other data from population studies [9][10][11][12][13][14] or may reflect difficulty in recognizing hypothyroid state in these patients or may be due to thyroid adaptive processes [15][16][17][18]. Possibly SMID patients, the targets of this study, might be at risk of developing disorders with a poor response of TSH that renders their hypothyroidism difficult to diagnose.…”
Section: Stagesupporting
confidence: 84%
“…Several investigators concluded that significant remission of thyroid function was brought about after IS, especially in iodine status [11][12][13][14]20]. In our study, however, statistically significant alteration of thyroid function was not detected even after the entire period of long-term IS, although short-term IS caused clear remission of thyroid dysfunction and significant UIC elevation in 5 HID cases.…”
Section: Resultscontrasting
confidence: 68%
“…[7][8][9][10] A number of studies also deal with the general health of high-altitude climbing Sherpas in Nepal. [11][12][13][14][15][16][17][18][19][20][21][22][23] These studies deal with various health topics, from epidemiology of hepatitis viruses [16] to iodine status in the Sherpa community. [20] However, no research was found that surveyed Sherpas' perceptions of their health in relation to *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20][21][22][23] These studies deal with various health topics, from epidemiology of hepatitis viruses [16] to iodine status in the Sherpa community. [20] However, no research was found that surveyed Sherpas' perceptions of their health in relation to *Corresponding author. Email: ewan.macdonald@glasgow.ac.uk their work.…”
Section: Introductionmentioning
confidence: 99%
“…Iodine deficiency (ID) may cause hypothyroidism which results in severe developmental delay in infants and stillbirth in pregnant women (1). In iodine deficient areas, which are distributed in fifty-four countries of the world, iodine supplementation programs using iodized salt have been implemented (2,3,4,5). …”
Section: Introductionmentioning
confidence: 99%